2018
DOI: 10.1002/jrs.5419
|View full text |Cite
|
Sign up to set email alerts
|

Hyper‐spectral Raman imaging correlating chemical substitution and crystallinity in biogenic hydroxyapatite: Dentin and enamel in normal and hypoplastic human teeth

Abstract: Micro‐Raman imaging and spectroscopy has become an established technique for the characterization of biogenic hydroxyapatite as, for example, the primary constituent of human teeth. However, few studies have yet gone beyond a qualitative analysis of the Raman response providing only limited insight into spatial heterogeneity of composition, structure, and degree of crystallinity. Here, we show how correlative electron microprobe and extended hyperspectral Raman imaging with high spatial and spectral resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 43 publications
0
20
2
Order By: Relevance
“…Also, FWHM gradually increases towards the pulp region within samples. For dentine, the spectral broadening of the ν1()normalPO43 band can be attributed to the carbonate substitution (b‐type) for the normalPO43 ions, which is believed to cause a loss of long‐range structural order . However, integral ratio maps (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Also, FWHM gradually increases towards the pulp region within samples. For dentine, the spectral broadening of the ν1()normalPO43 band can be attributed to the carbonate substitution (b‐type) for the normalPO43 ions, which is believed to cause a loss of long‐range structural order . However, integral ratio maps (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, higher FWHM values are also characteristic to caries lesions, in addition to blueshifted position and distorted (nonsymmetrical) line shape for the particular band . It is reported that peak position of ν1()normalPO43 generally increases towards inner subcomponents (from enamel to dentine) . Typical hydroxyapatite constituents such as fluoride and strontium can also affect the peak position of this band .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained were supported by vibrational analysis and indicate that IR and confocal Raman spectroscopy are important, useful, and fast tools to identify changes in the proteins' secondary structure in normal tissues, goiter, and follicular and papillary thyroid carcinomas . Wang et al implemented hyper‐spectral Raman imaging to correlate chemical substitution and crystallinity in biogenic hydroxyapatite for dentin and enamel in normal and hypoplastic human teeth . Zhao and Cai reported early detection of zinc deficit using confocal Raman spectroscopy.…”
Section: Biosciencesmentioning
confidence: 90%